Ocular symptoms of Saul — Wilson syndrome in children - L. V. Kogoleva; T. N. Vorontsova; Ju. A. Bobrovskaya (Российский офтальмологический журнал, 2022)
The genetic Saul — Wilson syndrome is so rare that the very few descriptions of its ocular manifestations available are of high clinical interest. Purpose. To offer a description of the ocular manifestations of the Saul — Wilson syndrome. Material and methods. Two children with a verified diagnosis of Saul — Wilson syndrome, observed from the age of 3 and 4 (the follow-up period was 6 months to 2.5 years), were subjected to a comprehensive ophthalmological examination. Results. The children, along with characteristic phenotypic manifestations (clubfoot, very short stature, short fingers and toes, hypermobile joints) were found to have a disordered visual system, associated with the particularities of the facial skeleton (exophthalmos or strabismus) and clinical and functional eye disorders: mild hypermetropia, hypermetropic astigmatism, partial complicated cataract. One child was diagnosed with changes in the structure and function of the retina, which indicates a dystrophic process. The diagnosis was genetically verified. Conclusion. Given the rarity of the disease, multiple organ involvement, an uncertain prognosis, an interdisciplinary approach to the management of such patients, constant dynamic monitoring and timely correction of detected disorders is necessary.